Essential Oil Components of Clove Raja Variant Flower Bud Oil (Syzygium aromaticum (L.) Merr. & L. M. Perry) in Mamala Village, Central Maluku Regency, Maluku Province - Mahulette, Asri Subkhan; Lating, Muhammad Fajri Aditthia; Wattimena, Anna Yuliana; Makaruku, Marlita Herlin (Jurnal Agrohut, 2024)
Clove Raja is classified as an intermediate clove type because it has morphological characteristics similar to cultivated-type cloves from the aromatic group and wild-type cloves from the non-aromatic group. The morphological similarity indicates similarities in the essential oil components between Raja clove, cultivated, and wild-type cloves. The study aims to identify the essential oil components of one of the Raja clove variants by comparing them with the results of previous essential oil component analysis in cultivated type cloves from the aromatic group represented by Tuni cloves and wild type cloves from the non-aromatic group represented by Hutan cloves. The material for distillation comes from the flower part of one of the Raja clove variants. Raja clove flower oil distillation was carried out using the steam-hydro distillation method. In contrast, the equipment for analyzing essential components used Gas Chromatography-Mass Spectrometry (GC-MS) in the form of Agilent Technologies 7890. The critical component data obtained were analyzed using R Stat 3.1.0 software to produce a heatmap profile of essential oil grouping. The results of the Gas Chromatography-Mass Spectrometry (GC-MS) analysis obtained seven crucial components of Raja cloves, namely eugenol (75.35%); caryophyllene (9.63%); Germacrene-D (3.73%); I-Isopropyl-4,7-dimethyl-1,2,3,5,6,8a—hexahydronaphtalene (1.65%); humulene (1.36%); 2'-3',4' trimethocyacetophenone (1.22%); α-cubebene (1%). The characteristic components of Raja clove oil in the heatmap profile are indicated as eugenol; germacrene-D; α-humulene; 2'-3',4' Trimethocyacetophenone, I-isopropyl-4,7-dimethyl-1,2,3,5,6,8a-hexahydronaphtalene. The identification results show that Raja cloves have similarities in the main component of eugenol with the results of previous studies on cultivated cloves represented by Tuni cloves, while the similarity to wild-type cloves represented by Hutan cloves is in the form of  germacrene-D.